2019
DOI: 10.1513/annalsats.201903-248oc
|View full text |Cite
|
Sign up to set email alerts
|

Return to Employment after Critical Illness and Its Association with Psychosocial Outcomes. A Systematic Review and Meta-Analysis

Abstract: The material cannot be used for any other purpose without further permission of the publisher and is for private use only. There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 69 publications
2
61
0
1
Order By: Relevance
“…1 As the population of ICU survivors has increased, research has shifted to understanding and improving outcomes of survivors and, in particular, on providing high-quality patient-and family-centered care (PFCC). [2][3][4][5][6][7] Such care is a target for reimbursement through value-based purchasing programs, forms a basis of the National Academy of Medicine's definition of health care quality, and is prioritized in research funded by the Patient-Centered Outcomes Research Institute. [8][9][10] However, there is no agreed-upon definition for PFCC in the ICU, and national, patient-reported quality assessments on hospital care do not specifically ask about ICU experiences.…”
mentioning
confidence: 99%
“…1 As the population of ICU survivors has increased, research has shifted to understanding and improving outcomes of survivors and, in particular, on providing high-quality patient-and family-centered care (PFCC). [2][3][4][5][6][7] Such care is a target for reimbursement through value-based purchasing programs, forms a basis of the National Academy of Medicine's definition of health care quality, and is prioritized in research funded by the Patient-Centered Outcomes Research Institute. [8][9][10] However, there is no agreed-upon definition for PFCC in the ICU, and national, patient-reported quality assessments on hospital care do not specifically ask about ICU experiences.…”
mentioning
confidence: 99%
“…This cohort had a significant burden of acute illness requiring prolonged mechanical ventilation and high rates of neuromuscular blockade. Despite this, we report meaningful early recovery including increased return to employment in a single centre, from a small sample [ 5 ]. However, caution should be taken with the interpretation of these outcomes, as employment status can fluctuate following critical illness [ 5 ].…”
mentioning
confidence: 99%
“…Despite this, we report meaningful early recovery including increased return to employment in a single centre, from a small sample [ 5 ]. However, caution should be taken with the interpretation of these outcomes, as employment status can fluctuate following critical illness [ 5 ]. Furthermore, HRQoL was similar to a previous ARDS cohort (Median HUS, 0.77) and better than a previous cohort of survivors from our own centre (Median HUS, 0.29) [ 3 , 6 ].…”
mentioning
confidence: 99%
“…A recent large, observational study reported that 64% and 56% of their cohort experienced one or more impairments in the domains of PICS, at 3 and 12 months, respectively ( 4 ). Such impairments prevent individuals from returning to their previous familial roles and impact return to employment ( 5 , 6 ). Ensuing morbidity has broad public health and societal implications ( 7 ).…”
mentioning
confidence: 99%